Constructing Tanghulu-like Diamond@Silicon carbide nanowires for enhanced thermal conductivity of polymer composite. (January 2022) - Qin, Yue; Wang, Bo; Hou, Xiao; Li, Linhong; Guan, Chunlong; Pan, Zhongbin; Li, Maohua; Du, Yuefeng; Lu, Yunxiang; Wei, Xianzhe; Xiong, Shaoyang; Song, Guichen; et al.
Abstract: Polymer composites with high thermal conductivity possess light weight, easy process and high chemical resistance, which has a huge demand in electronic packaging fields. Therefore, the development of new filler for improving the thermal conductivity has attracted lots of attentions in the field of polymer composites. In this work, a new hybrid filler was prepared through depositing nano-crystalline diamonds on SiC nanowires by hot filaments chemical vapor deposition. The results of SEM and TEM characterizations showed that the filler has a novel structure which is similar as a string of "sugar-coated haws on a stick" (a kind of Chinese candied fruit, named Tanghulu). Polymer composites containing the filler with the Tanghulu-like structure presented the high thermal conductivity of 0.57 W m −1  K −1 under 25 wt% filler contents. The excellent thermal conduction performance is attributed to the regional continuous networks formed by filler with the Tanghulu-like structure. Infrared images and a cooling radiator were utilized to further confirm the high thermal transportation performance of the polymer composites. The development of Tanghulu-like diamond@silicon carbide nanowires proposes a new strategy to prepare polymer composites with enhanced thermal conductivity, which will further promote the application in electronic packaging fields. Graphical abstract: Table of contents entry: Image 1 Highlights: A novel filler with Tanghulu-like structure was prepared through depositing nano-crystalline diamond on SiC nanowires. Regional continuous networks formed by the developed filler in PDMS composite improved the thermal conductivity. Infrared images and a heating radiator application demonstrated the excellent thermal performance of PDMS composites.